Deposition of graded SiO2/SiC coatings using high-velocity solution plasma spray - Miranda, F. S.; Caliari, F. R.; Campos, T. M.; Essiptchouk, A. M. [UNESP]; Filho, G. P. (Elsevier, 2017)
Carbon/carbon (C/C) composites are widely used in structural components, particularly in the aerospace and aeronautics sectors. However, the application of C/C composites is limited by low oxidation resistance at high temperatures. In order to overcome this problem, graded SiO2/SiC coatings were deposited on C/C composites by a high-velocity solution plasma spray (HVSPS) process. Graded coatings were formed by reactions between the Si(OH)4 sprayed liquid precursor and the C/C substrate; these reactions were promoted by the high temperature of the plasma torch. The morphologies, microstructures, and chemical compositions of the coatings were investigated by X-ray diffraction, Raman spectroscopy, Fourier-transform infrared spectroscopy, and scanning electron microscopy/energy-dispersive X-ray spectroscopy. By altering the deposition time, the coating thickness was controlled, therefore demonstrating SiC formation and realizing graded SiO2/SiC coatings.
Keywords: Ceramic coatings; Graded coatings; Solution plasma spray; Supersonic plasma torch